?TECHNIQUES FOR INTER-CALIBRATION OF DEAD WEIGHT PRESSURE TESTERS (Biological Sciences - PJSIR, 1995)
AsimpleandreliableapproachhasbeenmadetocalibrateandcertifyAir,OilorGas-operatedDeadWeightPressure Tester (DWPT) against a Reference Dead Weight Pressure Tester. Periodic calibration data of dead weight pressure testers of different ranges and make has been collected against a reference DWPT traceable to the'National Physical Laboratory, UKandNIST(NBS)USA.Usingthesetechniques,theuncertainties ofcalibratedDWPTshavebeenfound within their limits oferrorasspecified bythemanufacturer. The methodhasbeenfound suitableforthecertification of oil, gas, air-operated Dead Weight Pressure Testers using oil-operated DWPT asreference standard.